DIALEKTIKA PASANGAN HUBUNGAN ROMANTIS YANG BERKENALAN MELALUI APLIKASI KENCAN ONLINE TINDER - Martha Caesarin Putri Yulinta; Turnomo Rahardjo; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The improvement of technology provides easy access to establish relationships, one of which is the emergence of online dating applications such as Tinder. There are various reasons to use this application, it starts from expanding relationships to get into romantical partners, that makes 210 million people active as users in this application. However, the increasing cases of violence such as sexting, cyber harassment to fraud committed by certain individuals who use online dating applications cause anxiety for the users. Therefore, researchers examined further to find out how the dialectic occurs and the strategies used by couples who meet through the online application Tinder in dealing with the dialectic that occurs. In this study, researchers conducted data analysis using phenomenological methods and in-depth interview analysis techniques. Then, the theories used in this study are the Theory of Relational Dialectics by Lexlie Baxter and Barbera M. Montgomery, the Theory of Self Disclosure by West and Turner, and the Theory of Social Information Processing by Joseph B. Walther. The results of this study showed that the informants used the dating application Tinder for several reasons such as curiosity, finding new friends to life partners. Couples formed through these dating apps go through a series of stages that shape the dynamics of the dialectic experience as a couple in a romantic relationship. Where it is also related to the concepts from internal relational dialectics such as connectedness and separatedness, certainty and uncertainty, and also the openness and closedness. Furthermore, to deal with various dilemmas in establishing romantic relationships through this dating application, researchers found several responses and strategies used by informants, namely by balancing dialectical tension, carrying out temporary separation strategies, and separation of segments in life. By using these strategies, informants can relieve relationship tensions that arise and tend to accept and use the opportunity to increase understanding between partners and also strengthen the closeness of the relationship.